Solving Inverse Kinematics of the Shotcrete Manipulator Based on the Plane Two-Link Model and Trajectory Planning - Chunlei Luo; Yi He; Shitu Abubakar (Journal of Robotics)
Traditionally, the construction of tunnel support is to manually move the manipulator through the remote control. During the manual construction process, there is a large rebound rate and a reduction in the compactness of the concrete. Skilled operators can obtain better shot blasting quality, but training of a skilled worker is costly. In this study, an automatic shotcrete manipulator is proposed to complete spraying and improve the spraying quality. The model of the manipulator is simplified into a planar two-link manipulator, solved the inverse kinematics of the shotcrete manipulator, and implemented the automatic trajectory planning process. By simplifying the complex mechanical arm structure model into a simple planar two-link manipulator model, the inverse kinematics of the shotcrete manipulator is solved, and automatic trajectory planning software is developed, which can better help construction and reduce injury to personnel’s health and can also help the construction party save materials and improve economic efficiency and construction efficiency.